The Impact of Working Capital Management, Product Innovation, and Financial Management on MSME Business Sustainability in South Sulawesi - Syamsu Rijal; Supriandi, Supriandi (Westscience Press, 2024)
This study examines the impact of Capital Management, Financial Management, and Product Innovation on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in South Sulawesi, Indonesia. Amid increasing economic challenges, MSMEs must adopt effective financial and innovation strategies to achieve long-term sustainability. A quantitative approach was employed, using data from 255 MSMEs and analyzed through Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings indicate that all three factors positively and significantly affect MSME sustainability, with Financial Management showing the strongest influence, followed by Capital Management and Product Innovation. These results suggest that MSMEs need to balance financial planning, efficient capital management, and innovation to foster resilience and competitiveness. This study contributes to the literature by applying the Resource-Based View (RBV) theory to MSME sustainability, providing actionable insights for MSME managers and policymakers in resource-constrained environments.